2013
DOI: 10.1093/pch/18.10.e59
|View full text |Cite
|
Sign up to set email alerts
|

Modest treatment effects and high program attrition: The impact of interdisciplinary, individualized care for managing paediatric obesity

Abstract: An individualized, interdisciplinary weight management intervention led to weight stabilization and a modest weight reduction in children with obesity. Strategies to minimize program attrition are needed to optimize family engagement in care and success in managing paediatric obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
13
0
4
Order By: Relevance
“…Four Canadian weight management programs have published evaluations, which demonstrated statistically significant, clinically moderate weight loss effects but high rates of attrition ( Watson-Jarvis, Johnston & Clark, 2011 ; Panagiotopoulos et al, 2011 ; Ball et al, 2011 ; Avis et al, 2013 ). The Centre for Healthy Weights Shapedown BC obesity management program reports a significant change from weight gain to weight loss at the end of the program.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four Canadian weight management programs have published evaluations, which demonstrated statistically significant, clinically moderate weight loss effects but high rates of attrition ( Watson-Jarvis, Johnston & Clark, 2011 ; Panagiotopoulos et al, 2011 ; Ball et al, 2011 ; Avis et al, 2013 ). The Centre for Healthy Weights Shapedown BC obesity management program reports a significant change from weight gain to weight loss at the end of the program.…”
Section: Resultsmentioning
confidence: 99%
“…Participant BMI z-scores on average decreased from 2.14 to 2.08 ( Watson-Jarvis, Johnston & Clark, 2011 ). Program attrition in an interdisciplinary, individualized care weight management program in Edmonton, Alberta, was 49 and 73% at 7 and 11 months, with 8 and 5% of children showing BMI decreases at these time-points ( Avis et al, 2013 ). Given the considerable heterogeneity between studies with regard to sample characteristics, settings, interventions, and outcome measures, we estimated the probability of weight loss after completion of a lifestyle intervention at 30% with 10% and 50% as worst and best case estimates.…”
Section: Resultsmentioning
confidence: 99%
“…This population was younger (mean age 11.8 years) and less obese (mean BMI 37 kg m −2 ) than teens enrolled in STOMP but had a similar profile of baseline comorbidities . A recent study from Edmonton, Canada, reported very similar outcomes in 165 children age 5–18 years with no mean BMI z‐score change and a 73% attrition rate over 11 months .…”
Section: Discussionmentioning
confidence: 98%
“…the impact of negative personality traits in care delivery (35,69), and preferences or demands expressed on subjects unrelated to health, but related to certain aspects of daily life, when encountering a health issue (e.g. lifestyle changes to prevent childhood obesity) (61). They suggest that the usual characteristics of age, sex, clinical condition and education, may not predict how patients tolerate the adaptation of particular interventions (68), and call for opening up of patient characteristics used during segmentation analysis, and the type of data collected (67,83).…”
Section: Discussionmentioning
confidence: 99%
“…Research could also help structure the content of a customized intervention. Several articles underlined the importance of coordination and communication efforts in customizing interventions, in particular by emphasizing the role of structural integration or developing multidisciplinary teams (61,62,63). Other articles have stressed the importance of personalizing professional-patient relationships (85) while some others have stressed the key-role of modular packages (26).…”
Section: Discussionmentioning
confidence: 99%